The United States Demand for Imports of Materials, 1923-1960 - Reimer, Richard (The Review of Economics and Statistics, 1964)
PpT HE purpose of this study is to add to our empirical knowledge concerning the relationship between imports of materials and the level of economic activity and prices, as well as to make some quantitative estimates of the magnitude of the influence which these factors have in determining the volume and origin of this country's imports of materials.1 While most of the empirical work that has appeared in this area up to now has of necessity had to rely on pre-war data, a long enough time period has now elapsed since the end of World War II to permit the use of data from the postwar period in a statistical analysis.2 This study makes use of the unit value and quantity indexes of imports first computed by John H. Adler, Eugene R. Schlesinger, and Evelyn Van Westerborg in 1932.3 These indexes were computed for the years 1923 through 1950. Since that time Adler, now with the International Bank for Reconstruction and Development, and Charles G. Goor, also with the International Bank, have revised the indexes for 1949-50 and have carried them forward through 1953. As part of the present study, the indexes for total imports of materials and for imports of materials from seven geographic or political regions have been carried forward through 1960. The seven regions are: European Payments Union Countries, Other European Countries, Total Europe, Canada, Latin America, Overseas Sterling Area, and the Rest of the World. These indexes are given in Appendix B. The indexes were computed according to the Fisher Ideal index number formula and originally the years 1935-39 were used as the base period. However, after World War II it was found that the original sample of commodities no longer gave the desired coverage, and therefore additional commodities were added to the sample and the indexes were chained starting in 1949. For the period 1923-46, import data for computing the indexes was taken from the annual volumes of Foreign Commerce and Navigation of the United States, published by the Bureau of Foreign and Domestic Commerce. For the years 1947-60, the data was taken from the Bureau of the Census, Calendar Year Reports No. FT 110, United States Imports of Merchandise for Consumption. As is indicated by the use of regional indexes, this study attempts not only to analyze the demand for total imports of materials, but also the demand for imports of materials from various regions. Two of the more important reasons for the regional emphasis should be noted. First, even within the economic classification of materials the composition of imports from the various regions differs greatly. Given these differences in the composition of imports, there is ample reason why the level of United States industrial production and relative prices might affect the volume of imports coming from the various regions quite differently. A second reason for doing a study based on imports from various regions is the effect which a change in the volume of U.S. imports has on the exporting countries. The United States purchases a large share of the materials exports of various Latin American countries and Canada. Certain East European countries and some of the countries that were formerly colonies of West